ANALISIS KETERAMPILAN SCIENTIFIC COMMUNICATION SISWA SMA MELALUI PEMBELAJARAN STEM-SDGs PADA MATERI PEMANASAN GLOBAL - Afkarina, Dina; Aristya Putra, Pramudya Dwi; Lesmono, Albertus Djoko (Jurnal Pendidikan Fisika FKIP UM Metro, 2024)
Scientific communication is included in 21st century skills. This skill is important for students in order to be successful in science. One way to teach this skill by implementing STEM-SDGs learning. The 14th SDGs goal regarding ocean ecosystems can be conveyed through material on the physics of global warming. The aim of this research was to analyze the level of student’s scientific communication skills in discussing SDGs issues related to global warming through STEM learning. This research was a qualitative descriptive with a case method design. This research was conducted at SMAN Kalisat in the odd semester of the 2023/2024 academic year. The data collection method used were observation, interviews and documentation. The research data were analyzed using SG code. Based on the research results, it was found that STEM-SDGs learning can improved scientific communication skills. Scientific communication skills in indicators conveying specific natural phenomena increased from SG+ to SG++, indicators conveying scientific topics and representing scientific findings or evidence increased from SG- to SG++. However, the indicator for the use of scientific language terms tended to remain stable at SG-, showing no increase.